Research Trend In Islamic Financial Technology And Blockchain: A Bibliometric Analysis - Mohd Fauzi Abu-Husin; Kuni Afifah; Aam Slamet Rusydiana; Muhammad Bilal Zafar; Muhammad Hanif Mohd Noor; Siti Nurjanah Mastor Mustafa; Mohd Afandi Salleh (Universiti Sains Islam Malaysia, 2025)
Malaysian Journal of Syariah and Law, Volume 13 Issue 1 Page (147-163)